Effect of continuous antibiotic prophylaxis in children with postoperative JJ stents: A prospective randomized study. Issue 1 (February 2021) - Akinci, Aykut; Kubilay, Eralp; Solak, Vahid Talha; Karaburun, Murat Can; Baklaci, Can Utku; Aydoğ, Ezel; Soygür, Yakup Tarkan; Burgu, Berk
Summary: Objective: We aimed to investigate the effectiveness of continuous antibiotic prophylaxis (CAP) in patients with JJ stent and tried to identify the group that could specifically benefit from CAP by a prospective randomized study. Methods: A prospective, randomized, controlled, non-blind, non-placebo study was performed in a single center.A total of 105 patients who underwent surgery with JJ stent (PNL, URS, pyeloplasty, UNC) were randomized into two groups. 53 patients in Group A received CAP and 52 patients in Group B were controlled without CAP, during the presence of a JJ stent. Patients with external stents, nephrostomy tubes, indwelling long-term urethral catheters were excluded. History of preoperative use of CAP and lower urinary tract symptoms were noted. Trimethoprim/sulfamethoxazole (TMP/SMX) was used as the initial choice of antibiotic however if there was a history of antibiotic resistance in previous urinary cultures, Nitrofurantoin was administrated. Urinary cultures were obtained before surgery and before stent extraction. JJ stents were sent to culture. Symptomatic febrile urinary tract infections with positive urine cultures (10 5 CFU on a clean catch or 10 3 with urethral catheterization) were compared between groups. Discussion: Our study has some limitations; the study is the single-center, we did not follow-up of patients in terms of scar, there were low number of uncircumcised patients, multiple types of surgical procedures were performed. JJ stent is a frequently used instrument in children. Unfortunately, any randomized prospective on antibiotics administration while using a JJ stent is not available in the current literature. We hope our research will contribute to the existing literature and cause a significant change in clinical practice. Results: The mean age among all patients was 4.8 ± 3.9 years. The mean length of time jj stents stayed inside was 16.34 ± 6.45 days in group A and 15.29 ± 7.71 days in group B. The incidence of febrile urinary tract infections with CAP was significantly reduced (3.8% vs. 19% (p 0.015)). Multivariate regression analysis revealed that a positive history for preop febrile urinary tract infections and/or LUTS has a significantly higher association with the incidence of febrile urinary tract infecitons. Conclusions: CAP in the presence of JJ stents reduced the incidence of febrile urinary tract infections in a short period, especially in children with the previous history of febrile urinary tract infections and lower urinary tract symptoms. Summary table Rate Of Febrile Urinary Tract İnfection. Summary table   Total number Normal Febril infection (fUTI) Antibiotic (CAP) 53 51 2 No-Antibiotic 52 42 10